2011
DOI: 10.1016/j.bbamem.2011.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Folding studies of purified LamB protein, the maltoporin from the Escherichia coli outer membrane: Trimer dissociation can be separated from unfolding

Abstract: The folding mechanisms for β-barrel membrane proteins present unique challenges because acquisition of both secondary and tertiary structure is coupled with insertion into the bilayer. For the porins in Escherichia coli outer membrane, the assembly pathway also includes association into homotrimers. We study the folding pathway for purified LamB protein in detergent and observe extreme hysteresis in unfolding and refolding, as indicated by the shift in intrinsic fluorescence. The strong hysteresis is not seen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…This indicates that the dissociation of the dimer was not coupled with the unfolding of the protein. This phenomenon is consistent with recent unfolding studies on LamB, another β -barrel membrane protein, where the trimeric protein disassociated into folded monomeric species at low pH values, suggesting that trimer dis-association and unfolding of the protein may not occur simultaneously [44]. …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This indicates that the dissociation of the dimer was not coupled with the unfolding of the protein. This phenomenon is consistent with recent unfolding studies on LamB, another β -barrel membrane protein, where the trimeric protein disassociated into folded monomeric species at low pH values, suggesting that trimer dis-association and unfolding of the protein may not occur simultaneously [44]. …”
Section: Discussionsupporting
confidence: 91%
“…Trypsin resistance has been used in previous studies as a useful indicator of protein folding [44, 23]. We observed that the folded oligomeric and monomeric bands (Figure 4a) were resistant to trypsin digestion, while the unfolded band disappeared after trypsin treatment (Figure 4b).…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…Folding and unfolding of protein have been observed with the help of banding pattern obtained from the SDS-PAGE. 52-54 Baldwin et al 52 focused on the folded and unfolded proteins on SDS-PAGE and used to quantitate their unfolding.…”
Section: Study Of the Behaviour Of Trypsin At Molecular Level In The mentioning
confidence: 99%